Validity and reliability of the BeastTM sensor to measure movement velocity during the back squat exercise - Vallejo, F. T.; Chien, L. T.; Hébert-Losier, K.; Beaven, M. (The Journal of Sport and Exercise Science, 2020)
The purpose of this study was to analyze the validity and reliability of the BEAST™ wearable device to measure movement velocity during the back squat exercise. Eleven national-level female field-hockey players (age: 18.4 ± 1.7 y; back squat 1-RM: 92.7 ± 14.1 kg; height: 158.4 ± 4.6 cm; weight: 54.5 ± 5.5 kg) performed 3 repetitions of the back squat exercise with four loads on a power rack. Movement velocity for each repetition was simultaneously recorded using a linear position transducer (LPT) and the BEAST™ sensor. Results showed excellent agreement between the LPT and the BEAST™ for mean movement velocity and power, with intra-class correlation coefficient (ICC) values of 0.966 and 0.957, respectively; however, a systematic bias was observed with the BEAST™ sensor compared to the LPT device with greater mean velocity (+0.098 m·s-1, p < 0.001, 14.3%) and power (+51.8 W, p < 0.001, 21.9%). For repetitions at a given workload, mean velocity and power measures were highly reproducible for both the BEAST™ (velocity: ICC = 0.935, CV = 7.4%, power: ICC = 0.962, CV = 8.4%) and the LPT (velocity: ICC = 0.929, CV = 8.7%; power: ICC = 0.923, CV = 10.2%). The results support the use of the BEAST™ as a reliable low-cost wearable device to track velocity and power outputs during back squat training. Comparisons between data from the BEAST™ sensor and the LPT device should be made with caution due to the significant systematic bias observed. Wearable devices, such as the one used in this study, have valuable practical applications for athletes, strength and conditioning coaches, and sport scientists attempting to optimize training via feedback or monitor adaptations resultant from the manipulation of training micro-cycles and periodised plans.